Methods of chinese-spanish translations of Li Bai’s poems: Based on translations by Chen Guojian and Anne-Hélène Suárez Girard - Wu, Tong (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Li Bai is a relevant Chinese poet in the whole history of Chinese poetry, and numerous translations of his classical poems are currently emerging, among them, the translations of Chen Guojian and Anne-Hélène Suárez Girard stand out. Few researches have been devoted to the comparison of their translation versions, and it is a relevant approach to learn the different methods used by translators from both countries and has been an important inspiration for beginner translators to take advantage of both sides in order to achieve a better translation.